Loading and release of the complex [Pt(DTBTA)(DMSO)Cl]Cl·CHCl3 with the 2, 2′-dithiobis(benzothiazole) ligand into mesoporous silica and studies of antiproliferative activity on MCF-7 cells. (1st October 2018) - Rubino, Simona; Saladino, Maria Luisa; Busà, Rosalia; Chillura Martino, Delia Francesca; Girasolo, Maria Assunta; Caponetti, Eugenio; Tesoriere, Luisa; Attanzio, Alessandro
Graphical abstract: Complex(1 ) was encapsulated on MCM41 and MCM41-NH2 mesoporous silica. The mechanism of anchoring of MCM41-NH2 on the complex(1 ) was reported. Study of release was performed by using UV–Vis spectroscopy. The complex(1 )-conjugates were evaluated by MTT assay and cytofluorimetric assay. Abstract: Synthetic delivery systems have great potential for overcoming problems associated with systemic toxicity that accompanies chemotherapy with the use of cisplatin and family of platinum anticancer drugs. Mesoporous silicates have been studied in context of drug delivery and drug targeting. In this paper we report the studies of loading and release of a platinum complex, [Pt(DTBTA)(DMSO)Cl]Cl∙CHCl3 (1) where DTBTA = 2, 2′-dithiobis(benzothiazole), that was recently synthesized and structurally characterized. Evaluation in vitro of antitumor activity against a human breast cancer cell line (MCF-7) showed a very potent activity of complex(1 ). Therefore, we thought to incorporate this compound into MCM41 mesoporous silica and into analogous support functionalized with amino groups (MCM41-NH2 ). The complex(1 ) encapsulation efficiency % (EE%) in MCM41 and in MCM41-NH2, respectively, was evaluated by using UV–Vis spectroscopy. The porosimetry and IR spectra confirmed that the drug was within the pores in MCM-41 and that the complex(1 ) binds MCM41-NH2 with the aminopropyl functional groups of the mesoporous channels, respectively. The study of release was performed by using UV–Vis spectroscopy at 37 ± 1 °C in 0.1 M phosphate buffer solution (PBS) having pH 7.4 to simulate the physiological pH of blood. In order to investigate the efficacy of MCM-41/complex(1 ) and MCM41-NH2 /complex(1 ) conjugates, we have measured their ability to kill cancer cells of MCF-7 (human breast cancer). MTT test and cytofluorimetric assay of exposure of phosphatidylserine to the outer membrane were carried out to measure cytotoxicity and apoptosis induced by MCM41/complex(1 ) and MCM41-NH2 /complex(1 ). The investigated systems were very efficient for pharmaceutical controlled release and a promising agent for combination therapies.